2014
DOI: 10.1902/jop.2014.140070
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Lipopolysaccharide Upregulates Insulin Secretion From Pancreatic β Cell Line MIN6

Abstract: Background A close association between periodontitis and diabetes has been demonstrated in human cross-sectional studies, but an exact relationship between periodontitis and prediabetes has not been established. Previous studies using animal model systems consistently have shown that hyperinsulinemia occurs in animals with periodontitis compared to animals with healthy periodontium (while maintaining normoglycemia). Because bacterial lipopolysaccharide (LPS) plays an important role in the pathogenesis of perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 46 publications
5
28
4
3
Order By: Relevance
“…We previously reported that SerpinE1 was expressed in the MIN6 pancreatic β cell line in vitro and expression levels were significantly higher upon incubation of cells with Pg‐LPS or live Pg . The results from the current in vivo study demonstrated that SerpinE1 was minimally expressed in the islets of the control group but was highly expressed in the experimental group, supporting the results from our in vitro study.…”
Section: Discussionsupporting
confidence: 89%
“…We previously reported that SerpinE1 was expressed in the MIN6 pancreatic β cell line in vitro and expression levels were significantly higher upon incubation of cells with Pg‐LPS or live Pg . The results from the current in vivo study demonstrated that SerpinE1 was minimally expressed in the islets of the control group but was highly expressed in the experimental group, supporting the results from our in vitro study.…”
Section: Discussionsupporting
confidence: 89%
“…The results indicate that Pg LPS stimulates insulin secretion by MIN6 cells [11], further supporting the concept that periodontal pathogens influence IR. In addition, the results from a polymerase chain reaction array analysis identified a greater than 2-fold increase in Serpine1 gene expression by MIN6 cells upon stimulation with Pg LPS [11].…”
Section: Introductionsupporting
confidence: 61%
“…The results indicate that Pg LPS stimulates insulin secretion by MIN6 cells [11], further supporting the concept that periodontal pathogens influence IR. In addition, the results from a polymerase chain reaction array analysis identified a greater than 2-fold increase in Serpine1 gene expression by MIN6 cells upon stimulation with Pg LPS [11]. The Serpine1gene product SERPINE1, also known as Plasminogen activator inhibitor-1 (PAI1), is a serine protease inhibitor that inhibits tissue type and urokinase plasminogen activators (tPA and uPA respectively), thus functioning as an antifibrinolytic.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The doses of Pg ‐LPS investigated (0 to 1,000 ng/mL) were at the low end of the range used in in vitro and in vivo studies (0 to 50,000 ng/mL) 21 , 22 . Dolan et al 23 reported that healthy individuals had blood LPS levels ≥10 pg/mL.…”
Section: Discussionmentioning
confidence: 99%